Ultra-thick rolled copper foil with low roughness and high peel strength and preparation method thereof

By using composite additives and gradient pulse electroplating technology, the problems of high surface roughness and low peel strength of rolled copper foil have been solved, realizing the preparation of copper foil with low roughness and high peel strength, which is suitable for high-frequency signal transmission and current collectors for new energy vehicle batteries.

CN121046909APending Publication Date: 2025-12-02ZHEJIANG GARDEN NEW ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511263995.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing processes for preparing rolled copper foil suffer from problems such as high surface roughness, low peel strength, and severe environmental pollution from electroplating solutions, making it difficult to meet the requirements for high-frequency signal transmission and high bonding strength.

Method used

By combining composite additives with gradient pulse electroplating technology, the copper ion deposition kinetics are regulated through the synergistic effect of L-ascorbic acid, nanocellulose, trisodium citrate and sodium polyaspartate, and step-by-step gradient pulse electroplating is performed to form a dense nodule structure, achieving low roughness and high peel strength.

Benefits of technology

It significantly reduces the surface roughness of copper foil to Rz≤1.2μm, achieves a peel strength of over 1.5N/mm, improves the environmental friendliness of the electroplating solution system, and reduces wastewater treatment costs by 40%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of copper foil processing, in particular to an ultra-thick rolled copper foil with low roughness and high peel strength and a preparation method thereof. The quaternary composite additive composed of L-ascorbic acid, nanocellulose, trisodium citrate and sodium polyaspartate is introduced into the roughening liquid and the curing liquid, gradient pulse electroplating is combined, the surface roughness Rz of the obtained copper foil is smaller than or equal to 1.2 micrometers, the peel strength is larger than or equal to 1.5 N / mm, and the electroplating liquid is free of cyanide and heavy metal pollution. Through the synergistic effect of additive molecules and process optimization, the contradiction between low roughness and high stripping resistance is solved, and the method is suitable for the high-end fields of 5G high-frequency substrates, new energy automobile battery current collectors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of copper foil processing technology, and in particular to an ultra-thick rolled copper foil with low roughness and high peel strength, and its preparation method. Background Technology

[0002] In recent years, with the rapid development of the global new energy vehicle industry, the demand for high power and high current carrying capacity in power battery systems has increased significantly. To meet the requirements of fast charging technology, high-power printed circuit boards (PCBs), as core components, urgently need to use thick copper foil (3oz-6oz and above) to reduce the temperature rise effect under high load conditions. At the same time, 5G communication, millimeter-wave radar, and high-speed server fields have placed more stringent signal integrity requirements on high-frequency and high-speed PCBs: in the high-frequency band above 10GHz, the skin effect causes current to concentrate on the conductor surface, and excessively high copper foil surface roughness will significantly increase signal transmission loss and phase distortion, seriously affecting high-frequency signal integrity, such as eye diagram closure and increased bit error rate. However, existing ultra-thick copper foil production processes face bottlenecks in efficiency, performance, and environmental protection, which restricts the industry's technological upgrade.

[0003] Traditional electrolytic thick copper foil relies on electrodeposition for production, but it faces multiple constraints: First, the process efficiency is low, with a single foil production machine having an annual capacity of only 324 tons (based on 105μm), which is insufficient to meet the surging demand of the new energy vehicle market; Second, the electrolytic process is energy-intensive, and the cost of treating heavy metal wastewater is high, resulting in significant environmental pressure.

[0004] Rolled copper foil is produced through a casting-rolling process, offering significant advantages. Continuous rolling lines have an annual capacity of 24,000 tons (30% of which are 3oz-6oz), a 74-fold increase in capacity density compared to electrolytic methods. After multiple rolling and annealing processes, the copper foil's density, thermal conductivity, and surface finish are significantly optimized, resulting in superior mechanical strength and electrical conductivity. However, the excellent properties of rolled copper foil also present challenges for subsequent surface treatment. In PCB manufacturing, rolled copper foil undergoes roughening, chemical resistance treatment, and anti-oxidation treatment. Roughening directly determines the surface roughness and peel strength to the resin substrate after treatment. The core of roughening is to electroplate nodular copper particles onto the copper foil surface using high current density, high acid concentration, low copper ion concentration, and low-temperature electroplating conditions to increase surface roughness and improve adhesion to the resin substrate. However, if the surface roughness after roughening is too high, while it may temporarily improve adhesion strength, it will severely degrade high-frequency signal transmission performance.

[0005] Therefore, existing technologies urgently need to address the following key issues: (1) Insufficient bonding: The bonding force between the copper particles formed by the traditional roughening process and the rolled copper foil substrate is weak, which easily leads to the shedding of copper powder; (2) Conflict in roughness control: High-frequency and high-speed PCBs require low surface roughness to ensure electrical performance, but low roughness leads to insufficient resin bonding strength. Existing processes cannot achieve synergistic optimization of low roughness and high peel strength.

[0006] Researchers are exploring new additives and new electrolytic copper foil production processes to overcome the aforementioned problems. For example, application number CN201210031937.6 discloses an additive for electrolytic copper foil and a surface treatment process for very low profile electrolytic copper foil. By adding titanium sulfate as an additive, the deep plating capability of the electrolyte can be enhanced, and a uniform roughening layer can be plated at both the peak height and valley of the profile, enabling the produced very low profile electrolytic copper foil to achieve a microcrystalline effect. At the same time, the appropriate amount of various additives and suitable electroplating process conditions (copper acid content, temperature, current density) were determined, so that the treated 18-micron very low profile electrolytic copper foil can meet the following technical indicators: peel strength > 1.0 kg / cm and surface roughness Rz value ≤ 5.14 μm.

[0007] Application number CN202411655284.8 discloses a rolled copper foil and its surface electroplating method and application. By changing the electroplating process, it solves the problem of uneven particle distribution in the coating caused by the existing copper foil electroplating method, improves the performance of rolled copper, thereby reducing the difficulty and cost of subsequent precision manufacturing processes and improving overall production efficiency.

[0008] However, the above methods still cannot meet the requirements for copper foil with ultra-low profile and high peel strength. Summary of the Invention

[0009] To address the technical shortcomings of existing rolled copper foil manufacturing processes, such as high surface roughness, low peel strength, and severe environmental pollution from electroplating solutions, this invention proposes an ultra-thick rolled copper foil with low roughness and high peel strength, along with its preparation method. By combining the synergistic effect of composite additives with a gradient pulse electroplating process, the surface roughness of the copper foil is significantly reduced while effectively improving its peel strength, and the electroplating solution system achieves environmental friendliness.

[0010] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing ultra-thick rolled copper foil with low roughness and high peel strength, the method comprising the following steps: (1) The composite additive is prepared by mixing the following components in the following concentration ratios: L-ascorbic acid 0.5–2 g / L, nanocellulose 0.1–0.5 g / L, trisodium citrate 8–20 g / L, and sodium polyaspartate 2–10 g / L. The nanocellulose has a diameter of 30–80 nm and a surface hydroxyl density of 2.5–3.5 mmol / g. Finally, all components are dissolved in the addition tank to form a solution. The additive regulates the copper ion deposition kinetics through molecular synergy, achieving grain refinement, and is free of cyanide and heavy metal components.

[0011] (2) Add the composite additive from step (1) to the roughening electroplating solution. The roughening electroplating solution also contains 50-100 g / L of copper sulfate and 120-150 g / L of sulfuric acid. The pH of the roughening electroplating solution is 1.5-3.0.

[0012] (3) Add the composite additive from step (1) to the curing electroplating solution. The curing electroplating solution also contains copper sulfate 70-120 g / L and sulfuric acid 80-120 g / L. The pH of the curing electroplating solution is 1.5-3.0.

[0013] (4) Select rolled copper foil with a thickness of 105–210 μm. After filtering, inject the roughening electroplating solution from step (2) into the roughening tank. Use gradient pulse electroplating: forward current density 5–10 A / dm², reverse duty cycle 10%–30%, frequency 50–100 Hz, process parameters: temperature 35–65℃, copper foil travel speed 6–18 m / min, to perform one roughening treatment. A rough copper nodule structure is initially formed on the copper foil, which is the basis for improving the peel strength.

[0014] (5) Adjust the pulse parameters to a forward current density of 5-8 A / dm², a reverse duty cycle of 20%-40%, and a frequency of 50-120 Hz. The process parameters are: temperature 35-65℃ and copper foil travel speed 6-18 m / min. Secondary roughening is then performed. Based on the nodules formed in the first roughening, further increasing the nodule density and refining the nodule structure is a key step in achieving low roughness while maintaining high peel strength.

[0015] (6) Place the ultra-thick rolled copper foil in the curing electroplating solution of step (3) and perform gradient pulse electroplating: forward current density 3-8 A / dm², reverse duty cycle 15%-40%, frequency 80-120 Hz, copper foil travel speed 6-18 m / min, and perform a first curing treatment. On the fine nodule layer formed by the second roughening, cover with a denser and smoother copper layer.

[0016] (7) Adjust the pulse parameters to a forward current density of 3-5 A / dm², a reverse duty cycle of 15%-35%, a frequency of 80-150 Hz, and a copper foil travel speed of 6-18 m / min, and perform a secondary curing process. Further smoothing and densifying the primary cured layer is the decisive step in finally achieving an ultra-low roughness Rz≤1.2 μm.

[0017] (8) Obtain ultra-thick rolled copper foil after coarse curing treatment.

[0018] In the above process, L-ascorbic acid, as a green reducing agent, inhibits excessive deposition of copper ions and reduces microcracks; nanocellulose forms nanoscale nucleation sites through the coordination of surface hydroxyl groups with copper ions, limiting excessive grain growth and thus guiding the formation of uniform nanoscale protrusions; trisodium citrate and sodium polyaspartate synergistically regulate the copper ion complexation-dissociation balance and work synergistically with pulse electroplating to achieve grain refinement, resulting in copper foil with a surface roughness Rz≤1.2μm, which is more than 50% lower than the traditional process, a dielectric constant (1GHz) ≤3.5 during high-frequency signal transmission, and a peel strength stable above 1.5N / mm. The electroplating solution system eliminates cyanide and heavy metal additives, the biodegradability rate of the composite additive is >80%, and the wastewater treatment cost is reduced by 40% compared with the traditional process containing cyanide / heavy metals.

[0019] Furthermore, the nanocellulose is dispersed in ethylene glycol under ultrasonic power of 300–500 W for 30–60 min, resulting in a surface hydroxyl density of 2.5–3.5 mmol / g. The sodium polyaspartate has a molecular weight of 1000–5000 Da, and the molar ratio of sodium polyaspartate to trisodium citrate is 1:2 to 1:5. The purpose of this step is to precisely control the effect of the additives to ensure ideal nanoscale structure control during copper foil electrodeposition.

[0020] Furthermore, the filtration process employs a three-stage filtration system with pore sizes of 10μm, 5μm, and 1μm, respectively. This removes particulate impurities from the plating solution, preventing them from causing defects or rough spots on the copper foil surface and ensuring the smoothness and uniformity of the plating layer.

[0021] Furthermore, the waveform of gradient pulse electroplating is a square wave, with a forward pulse width of 5–10 ms and a reverse pulse width of 1–3 ms. This allows for better control of the deposition and dissolution time ratio within each pulse cycle, influencing nucleation density and growth morphology. Compared with the prior art, the present invention has the following advantages: This invention utilizes a pulse electroplating process with composite additives and parameter gradient adjustments to achieve a fine nodule and an ultra-smooth surface with an Rz ≤ 1.2 μm, ultimately yielding a copper foil with ultra-low profile and high peel strength. Simultaneously, a two-step roughening and two-step curing process is employed, with step-by-step / gradual gradient adjustments to key parameters to precisely control the formation process of the plating structure. Compared to a single-step process, this strategy can more accurately optimize the final performance. The resulting ultra-thick electrolytic copper foil has a thickness of 105–210 μm, an Rz ≤ 1.2 μm, and a peel strength ≥ 1.5 N / mm, making it particularly suitable for high-performance applications requiring ultra-low profile and low loss, such as 5G / 6G high-frequency substrates, and high peel strength and stability, such as current collectors in new energy vehicle batteries. Detailed Implementation

[0022] The invention can be further understood through the specific embodiments and comparative embodiments given below. However, they are not intended to limit the invention.

[0023] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this invention can all be purchased commercially.

[0024] Example 1 A method for preparing ultra-thick rolled copper foil with low roughness and high peel strength, the method comprising the following steps: (1) The composite additive was prepared by mixing the following components in the following concentration ratio: L-ascorbic acid 0.5 g / L, nanocellulose 0.1 g / L, trisodium citrate 8 g / L, and sodium polyaspartate 2 g / L. The nanocellulose had a diameter of 30–80 nm and was dispersed in ethylene glycol under ultrasonic power of 300 W for 50 min. The surface hydroxyl density was 2.5 mmol / g. The sodium polyaspartate had a molecular weight of 1000 Da and a molar ratio of sodium polyaspartate to trisodium citrate of 1:2.48. Finally, the components were dissolved in the addition tank to form a solution.

[0025] (2) Add the composite additive from step (1) to the roughening solution. The roughening solution also contains 60 g / L copper sulfate and 150 g / L sulfuric acid. The pH of the roughening solution is 1.5 and the temperature of the roughening solution is 54℃.

[0026] (3) Add the composite additive from step (1) to the curing solution. The curing solution also contains 120 g / L copper sulfate and 120 g / L sulfuric acid. The pH of the curing solution is 3.0 and the temperature of the curing solution is 54℃.

[0027] (4) The roughening electroplating solution from step (2) is injected into the roughening tank after being filtered through a three-stage filter. The pore sizes of the three-stage filter are 10μm, 5μm, and 1μm, respectively. A rolled copper foil with a surface roughness Rz of 105μm and a surface roughness of 0.5μm and an anode plate are selected and placed in the roughening solution. The power supply is turned on, and a square wave pulse power supply is used. The forward current density is set to 7A / dm², the reverse duty cycle is 30%, and the frequency is 100Hz. Electroplating is then started for the first roughening step. The temperature of the roughening solution is 54℃, and the copper foil travel speed is 10m / min.

[0028] (5) Immerse the rolled copper foil and anode plate after the first roughening treatment in step (4) in the roughening tank of the roughening solution in step (2), turn on the power, use a square wave pulse power supply, set the forward current density to 6A / dm², the reverse duty cycle to 40%, and the frequency to 120Hz, and start electroplating to perform the second roughening treatment. The temperature of the roughening solution and the copper foil travel speed are as in step (4).

[0029] (6) Immerse the rolled copper foil and anode plate after the secondary roughening treatment in step (5) in the curing solution of step (3), turn on the power supply, use a square wave pulse power supply, set the forward current density to 5A / dm², the reverse duty cycle to 20%, and the frequency to 90Hz, and start electroplating to perform a first curing treatment. The curing solution temperature is 54℃ and the copper foil travel speed is 10m / min.

[0030] (7) Immerse the rolled copper foil and anode plate after the first curing treatment in step (6) in the curing solution of step (3), turn on the power supply, use a square wave pulse power supply, set the forward current density to 4A / dm², the reverse duty cycle to 15%, and the frequency to 80Hz, and start electroplating to perform a second curing treatment. The temperature of the curing solution and the copper foil travel speed are the same as in step (6) to obtain an ultra-thick rolled copper foil after coarse curing treatment.

[0031] In this embodiment, no obvious copper powder shedding was observed in the rolled copper foil after the coarse curing treatment. The performance of the rolled copper foil after the coarse curing treatment obtained in this embodiment was tested, and the results are shown in Table 1.

[0032] Example 2 A method for preparing ultra-thick rolled copper foil with low roughness and high peel strength, the process flow of which includes the following steps: (1) The composite additive was prepared by mixing the following components in the following concentration ratio: L-ascorbic acid 2 g / L, nanocellulose 0.5 g / L, trisodium citrate 20 g / L, and sodium polyaspartate 10 g / L. The nanocellulose had a diameter of 30–80 nm and was dispersed in ethylene glycol under ultrasonic power of 500 W for 60 min. The surface hydroxyl density was 3.5 mmol / g. The sodium polyaspartate had a molecular weight of 3000 Da and a molar ratio of 1:1.20 to sodium citrate. Finally, all components were dissolved in the addition tank to form a solution.

[0033] (2) Add the composite additive from step (1) to the roughening solution. The roughening solution also contains 70 g / L copper sulfate and 120 g / L sulfuric acid. The pH of the roughening solution is 2.0 and the temperature of the roughening solution is 60℃.

[0034] (3) Add the composite additive from step (1) to the curing solution. The curing solution also contains 100g / L copper sulfate and 100g / L sulfuric acid. The pH of the curing solution is 3.0 and the temperature of the curing solution is 60℃.

[0035] (4) The roughening electroplating solution from step (2) is injected into the roughening tank after being filtered through a three-stage filtration system. The pore sizes of the three-stage filtration system are 10 μm, 5 μm, and 1 μm, respectively. A rolled copper foil with a surface roughness Rz of 210 μm and a surface roughness Rz of 0.8 μm is selected and placed in the roughening solution containing step (2). The power supply is turned on, and a square wave pulse power supply is used. The forward current density is set to 10 A / dm², the reverse duty cycle is 25%, and the frequency is 95 Hz. Electroplating is then started for the first roughening step. The temperature of the roughening solution is 60℃, and the copper foil travel speed is 15 m / min.

[0036] (5) Immerse the rolled copper foil and anode plate after the first roughening treatment in step (4) in the roughening tank of the roughening solution in step (2), turn on the power, use a square wave pulse power supply, set the forward current density to 8A / dm², the reverse duty cycle to 35%, and the frequency to 110Hz, and start electroplating to perform the second roughening treatment. The temperature of the roughening solution and the copper foil travel speed are as in step (4).

[0037] (6) Immerse the rolled copper foil and anode plate after the secondary roughening treatment in step (5) in the curing solution of step (3), turn on the power supply, use a square wave pulse power supply, set the forward current density to 5A / dm², the reverse duty cycle to 30%, and the frequency to 100Hz, and start electroplating to perform a first curing treatment. The curing solution temperature is 60℃ and the copper foil travel speed is 15m / min.

[0038] (7) Immerse the rolled copper foil and anode plate after the first curing treatment in step (6) in the curing solution of step (3), turn on the power supply, use a square wave pulse power supply, set the forward current density to 3A / dm², the reverse duty cycle to 20%, and the frequency to 120Hz, and start electroplating to perform a second curing treatment. The temperature of the curing solution and the copper foil travel speed are the same as in step (6) to obtain an ultra-thick rolled copper foil after coarse curing treatment.

[0039] In this embodiment, no obvious copper powder shedding was observed in the rolled copper foil after the coarse curing treatment. The performance of the rolled copper foil after the coarse curing treatment obtained in this embodiment was tested, and the results are shown in Table 1.

[0040] Example 3 The preparation process is basically the same as in Example 1, with the only difference being: Step (1) Preparation of the composite additive: The components are prepared according to the following concentration ratio: L-ascorbic acid 1g / L, nanocellulose 0.3g / L, trisodium citrate 10g / L, and sodium polyaspartate 5g / L. The nanocellulose has a diameter of 30-80nm, is dispersed in ethylene glycol, and subjected to ultrasonic treatment at 300W for 50min, resulting in a surface hydroxyl density of 3mmol / g. The sodium polyaspartate has a molecular weight of 6000Da, and the molar ratio of sodium polyaspartate to trisodium citrate is 1:1.20. Finally, all components are dissolved into a solution in the addition tank.

[0041] In this embodiment, no obvious copper powder shedding was observed in the rolled copper foil after the coarse curing treatment. The performance of the rolled copper foil after the coarse curing treatment obtained in this embodiment was tested, and the results are shown in Table 1.

[0042] Example 4 The preparation process is basically the same as in Example 1, with the only difference being: Step (1) Preparation of the composite additive: The components are prepared according to the following concentration ratio: L-ascorbic acid 0.5 g / L, nanocellulose 0.1 g / L, trisodium citrate 8 g / L, and sodium polyaspartate 2 g / L. The nanocellulose has a diameter of 30–80 nm and is dispersed in ethylene glycol using an ultrasonic power of 300 W for 50 min, resulting in a surface hydroxyl density of 2.5 mmol / g. The sodium polyaspartate has a molecular weight of 1000 Da, and the molar ratio of sodium polyaspartate to trisodium citrate is 1:2.48. Finally, all components are dissolved in the addition tank to form a solution.

[0043] In this embodiment, no obvious copper powder shedding was observed in the rolled copper foil after the coarse curing treatment. The performance of the rolled copper foil after the coarse curing treatment obtained in this embodiment was tested, and the results are shown in Table 1.

[0044] Comparative Example 1 A traditional roughening and curing process for rolled copper foil includes the following steps: (1) Preparation of roughening solution: The base solution is a copper sulfate-sulfuric acid system with the addition of traditional sulfur-containing additives. The composition of the roughening solution is: 96 g / L copper sulfate, 155 g / L sulfuric acid, 4 g / L gelatin, 0.45 g / L thiourea, 38 ppm chloride ions (added in the form of HCl), the pH of the roughening solution is adjusted to 1.2 with sulfuric acid, and the temperature of the electroplating solution is 55.7℃.

[0045] (2) Preparation of curing solution: The base solution is a copper sulfate-sulfuric acid system with formaldehyde additives. The curing solution consists of: 136 g / L copper sulfate, 99 g / L sulfuric acid, 12 ml / L formaldehyde (37% aqueous solution), and 0.15 g / L sodium dodecyl sulfate. The pH of the curing solution is 1.5, and the temperature of the electroplating solution is 53.8℃.

[0046] (3) Roughening treatment: A rolled copper foil with a thickness of 210 μm and a surface roughness Rz of 1.2 μm was placed in a roughening tank along with a lead alloy anode plate. A DC power supply was used, with a current density of 12 A / dm², a roughening time of 5 minutes, a copper foil travel speed of 6 m / min, and a roughening solution temperature of 56.5℃. Traditional processes typically involve only a single roughening step, and the high current density leads to coarse copper crystals.

[0047] (4) Curing treatment: The roughened copper foil was transferred to a curing tank using a DC power supply, with a current density of 6 A / dm², a curing time of 5 minutes, a copper foil travel speed of 6 m / min, and a curing solution temperature of 56.5℃. Traditional processes typically involve a single curing cycle without graded control.

[0048] (5) Post-processing: After curing, the copper foil is washed with water and dried to obtain the finished product.

[0049] In this embodiment, the rolled copper foil after coarse curing treatment showed obvious copper powder shedding. The performance of the rolled copper foil after coarse curing treatment obtained in this embodiment was tested, and the results are shown in Table 1.

[0050] Table 1. Performance test data of rolled copper foil prepared in the examples and comparative examples. Group Roughness (Rz) μm Peel strength / N / mm Copper powder situation Example 1 1.19 1.8 Copper powder does not fall off Example 2 1.11 1.9 Copper powder does not fall off Example 3 1.15 1.8 Copper powder does not fall off Example 4 1.16 1.8 Copper powder does not fall off Comparative Example 1 3.51 1.2 Copper powder detachment As can be seen from Examples 1-4, the ultra-thick rolled copper foil prepared in Examples 1-4 has a roughness Rz≤1.2μm, a peel strength≥1.5N / mm, and the copper powder does not fall off.

[0051] As can be seen from Examples 1-4, ultra-thick rolled copper foil with a molar ratio of sodium polyaspartate to trisodium citrate of 1:2 to 1:5 has lower roughness and higher peel strength.

[0052] As can be seen from Examples 1-4 and Comparative Example 1, the ultra-thick rolled copper foil prepared in Examples 1-4 has lower roughness, higher peel strength, and no copper powder shedding compared with the ultra-thick rolled copper foil prepared in Comparative Example 1. Furthermore, the electroplating solution system in the examples is environmentally friendly and does not contain cyanide or heavy metal components.

[0053] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.

Claims

1. A composite additive, characterized in that, The composite additive comprises the following components in the following concentration ratio: L-ascorbic acid 0.5-2 g / L, nanocellulose 0.1-0.5 g / L, trisodium citrate 8-20 g / L, and sodium polyaspartate 2-10 g / L, wherein the nanocellulose has a diameter of 30-80 nm.

2. The composite additive according to claim 1, characterized in that, The nanocellulose is dispersed in ethylene glycol and subjected to ultrasonic treatment with a power of 300-500W for 30-60 minutes, resulting in a surface hydroxyl density of 2.5-3.5 mmol / g. The sodium polyaspartate has a molecular weight of 1000-5000 Da and a molar ratio of sodium polyaspartate to trisodium citrate of 1:2 to 1:

5.

3. The composite additive according to claim 1, wherein the composite additive comprises the following components in the following concentration ratio: L-ascorbic acid 2g / L, nanocellulose 0.5g / L, trisodium citrate 20g / L, and sodium polyaspartate 10g / L.

4. A roughening electroplating solution based on composite additives, characterized in that, The roughening electroplating solution contains the composite additive as described in any one of claims 1 to 3, and also contains the following components in the following concentration ratio: 50-100 g / L copper sulfate and 120-150 g / L sulfuric acid, and the pH of the roughening electroplating solution is 1.5-3.

0.

5. A curing electroplating solution based on composite additives, characterized in that, The curing electroplating solution contains the composite additive as described in any one of claims 1 to 3, and also contains the following components in the following concentration ratio: copper sulfate 70-120 g / L, sulfuric acid 80-120 g / L, and the pH of the curing electroplating solution is 1.5-3.

0.

6. A method for preparing ultra-thick rolled copper foil with low roughness and high peel strength, characterized in that, To process ultra-thick rolled copper foil of 105–210 μm using the roughening electroplating solution according to claim 4 and the curing electroplating solution according to claim 5, the specific steps are as follows: (1) First roughening treatment: The roughening electroplating solution according to claim 4 is filtered and injected into the roughening tank, and gradient pulse electroplating is adopted: forward current density 5~10A / dm², reverse duty cycle 10%~30%, frequency 50~100Hz, process parameters: temperature 35~65℃, copper foil walking speed 6~18m / min. (2) Secondary roughening treatment: Adjust the pulse parameters to a forward current density of 5-8 A / dm², a reverse duty cycle of 20%-40%, a frequency of 50-120 Hz, and process parameters: temperature of 35-65℃ and copper foil travel speed of 6-18 m / min. (3) First curing treatment: The ultra-thick rolled copper foil is placed in the curing electroplating solution according to claim 5, and gradient pulse electroplating is adopted: forward current density 3-8A / dm², reverse duty cycle 15%-40%, frequency 80-120Hz, and copper foil walking speed 6-18m / min. (4) Secondary curing treatment: Adjust the pulse parameters to a forward current density of 3-5 A / dm², a reverse duty cycle of 15%-35%, a frequency of 80-150 Hz, and a copper foil travel speed of 6-18 m / min.

7. The method for preparing ultra-thick rolled copper foil with low roughness and high peel strength according to claim 6, characterized in that, The filtration is a three-stage filtration system with pore sizes of 10μm, 5μm, and 1μm, respectively.

8. The method for preparing ultra-thick rolled copper foil with low roughness and high peel strength according to claim 7, characterized in that, The waveform of the gradient pulse electroplating is a square wave, with a positive pulse width of 5-10 ms and a negative pulse width of 1-3 ms.

9. A low-roughness, high-peel-strength ultra-thick rolled copper foil, characterized in that, Prepared by the method according to any one of claims 6 to 8, Rz≤1.2μm, peel strength≥1.5N / mm.

10. The application of the low-roughness, high-peel-strength ultra-thick rolled copper foil according to claim 9 in 5G high-frequency substrates or current collectors for new energy vehicle batteries.

Citation Information

Patent Citations

  • Additive for electrolytic copper foil and surface treatment process of very low profile electrolytic copper foil

    CN102560584B

  • Rolled copper foil and surface electroplating method and application thereof

    CN119530909A

  • Preparation method of electronic copper foil

    CN104651885A

  • Surface blackening treatment method for rolled copper foil

    CN106191980A

  • Production method of strippable carrier copper foil

    CN117926350A